Habitat fragmentation influences genetic diversity and differentiation: Fine‐scale population structure of Cercis canadensis (eastern redbud). Issue 8 (16th March 2020) - Ony, Meher A.; Nowicki, Marcin; Boggess, Sarah L.; Klingeman, William E.; Zobel, John M.; Trigiano, Robert N.; Hadziabdic, Denita
Abstract: Forest fragmentation may negatively affect plants through reduced genetic diversity and increased population structure due to habitat isolation, decreased population size, and disturbance of pollen‐seed dispersal mechanisms. However, in the case of tree species, effective pollen‐seed dispersal, mating system, and ecological dynamics may help the species overcome the negative effect of forest fragmentation. A fine‐scale population genetics study can shed light on the postfragmentation genetic diversity and structure of a species. Here, we present the genetic diversity and population structure of Cercis canadensis L. (eastern redbud) wild populations on a fine scale within fragmented areas centered around the borders of Georgia–Tennessee, USA. We hypothesized high genetic diversity among the collections of C. canadensis distributed across smaller geographical ranges. Fifteen microsatellite loci were used to genotype 172 individuals from 18 unmanaged and naturally occurring collection sites. Our results indicated presence of population structure, overall high genetic diversity ( H E  = 0.63, H O  = 0.34), and moderate genetic differentiation ( F ST  = 0.14) among the collection sites. Two major genetic clusters within the smaller geographical distribution were revealed by STRUCTURE. Our data suggest that native C. canadensis populations in the fragmented area around the Georgia–Tennessee border were able to maintain high levels of genetic diversity, despite the presence of considerable spatial genetic structure. As habitat isolation may negatively affect gene flow of outcrossing species across time, consequences of habitat fragmentation should be regularly monitored for this and other forest species. This study also has important implications for habitat management efforts and future breeding programs. Abstract : In this study, we used microsatellite loci to estimate genetic diversity of Cercis canadensis L. (eastern redbud) wild populations on a fine scale. Our data reveal that current isolated patches and remnant populations are genetically stable and capable of maintaining viable populations at a geographically fine‐scale level. Forest fragmentation may cause a number of negative effects including, but not limited to, reduced genetic diversity and population size, increased population structure due to habitat isolation, and potential disruption of pollen‐seed dispersal.